Bodyweight change and its association with food and beverage consumption at the beginning COVID-19 confinement. (December 2022) - Cavagnari, Brian M.; Vinueza-Veloz, María Fernanda; Carpio-Arias, Valeria; Durán-Agüero, Samuel; Ríos-Castillo, Israel; Nava-González, Edna J.; Pérez-Armijo, Patricio; Camacho-López, Saby; Mauricio-Alza, Saby; Bejarano-Roncancio, Jhon Jairo; Núñez-Martínez, Beatríz; González-Medina, Gabriel; et al.
Summary: Objectives: SARS-CoV-2, a newly identified coronavirus responsible for the COVID-19 pandemic, has challenged health services and profoundly impacted people's lifestyles. The objective of the present study was to evaluate the effect of confinement during the COVID-19 pandemic on food consumption patterns and body weight in adults from 12 Ibero-American countries. Methods: Multicentric, cross-sectional study. Data was collected using an online survey disseminated by social networks. The sample included 10 552 people from Spain and 11 Latin American countries who were selected by snowball sampling. Results: While 38.50% of the sample reported weight gain, 16.90% reported weight lost. Weight change was associated with sex, age, country of residence, and education level. People who were not confined more often reported having maintained their weight in comparison to people who were confined. All Latin American countries showed an increased consumption of sweetened drinks, pastry products, fried foods, and alcoholic beverages during confinement. Consumption of eggs and dairy products was independent from body weight change. People who consumed more fruits and vegetables during confinement more often reported having lost weight. In contrast, body weight gain during confinement was associated with increased intake of sugary drinks, baked goods and pastries, pizza, fried foods, and alcoholic beverages. Conclusion: During COVID-19 confinement, the Latin American countries included in this study showed a change in their consumption patterns toward less healthy diets, which in turn was associated with an increase in the body weight of their population.